APPLICATION OF THE AHP-PROMETHEE METHOD FOR SELECTING THE OPTIMAL ELECTRIC VEHICLE FOR URBAN TRANSPORTCTRIC VEHICLE FOR URBAN TRANSPORT - Ilić, Ivana; Ilić, Dejan; Ilić, Ines; Mihajlović, Aleksandar (The European Journal of Applied Economics, 2024)
This study elucidates the findings derived from the implementation of the integrated AHP-PROMETHEE multi-criteria decision-making method aimed at selecting the most suitable electric vehicle for urban transport. The AHP methodology facilitated the identification of critical criteria influencing the selection of an electric vehicle for urban use, including factors such as price, battery warranty, charging speed, acceleration to 100 km/h, maximum speed, engine power, efficiency, battery performance, and mileage. The subsequent application of the PROMETHEE method allowed for the ranking of nine electric vehicles based on these established criteria. Each vehicle alternative was assessed regarding its capacity to fulfill the specified requirements and preferences of the decision-makers. The analysis revealed that the Mini Cooper E emerged as the model that most effectively aligns with the prioritized criteria. This vehicle is deemed the optimal selection for urban transport needs, considering all pertinent factors. The decision to select a specific electric vehicle is expected to influence the efficiency, sustainability, and economic viability of the urban transportation system. Furthermore, it is advisable to maintain ongoing surveillance of advancements in electric vehicle technology and charging infrastructure to ensure that the selected model continues to represent the best option in the future.